A study of the Ca antigen in epithelial tumours of the ovary. Issue 1 (January 1984) - Ferguson, A M; Fox, H
Abstract : The expression of Ca antigen in ovarian epithelial tumours has been studied by an immunohistochemical technique using the Ca 1 monoclonal antibody. The antigen was found to be present in some examples of each of the histological subtypes of ovarian epithelial neoplasms and was detected in benign, borderline and malignant tumours. It is concluded that the presence of Ca antigen is of no discriminatory value in the assessment of malignancy in ovarian epithelial neoplasms.